Enterobius vermicularis Infection in a Child Population with Evidence of Vulvovaginitis and Bacterial Coinfection in Girls in Oaxaca, México - Jaime Vargas-Arzola; Aristeo Segura-Salvador; Luis Alberto Hernández-Osorio; Nancy G. Santos-Hernández; Dolores G. Vidal-López; Adriana Moreno-Rodríguez; José A. De Fuentes-Vicente (Hindawi Limited, 2024)
Infection by the nematode Enterobius vermicularis (Enterobiasis) is the most common helminth parasitosis in humans. It is closely related to poverty, and a higher prevalence is observed in children, in those who can cause important complications. Due to this, we evaluated the prevalence of Enterobiasis in children from a marginalized community in southeastern Mexico. Additionally, we analyzed possible cases of ectopic infection in girls and the presence of coinfections with other pathogens. Of 904 children, we found a prevalence of 21%, being higher in girls than in boys. Additionally, we determined the presence of E. vermicularis in the vagina of 11 girls who had mild lesions and coinfections with bacteria. Our findings highlight the importance of developing prevention and surveillance programs in areas of extreme poverty.